Experimental and numerical evaluations of composite concrete-to-concrete interfacial shear strength under horizontal and normal stresses - M. Yahya, Al-Fasih; Mazizah E., Mohamad; Izni Syahrizal, Ibrahim; Y., Ahmad; M. A., Mohd Ariffin; Noor Nabilah, Sarbini; Roslli Noor, Mohamed; Ahmad Kueh, Beng Hong (PLOS, 2021)
Effects of different surface textures on the interface shear strength, interface slip, and failure modes of the concrete-to-concrete bond are examined through finite element numerical model and experimental methods in the presence of the horizontal load with ‘push-off’ technique under different normal stresses. Three different surface textures are considered; smooth, indented, and transversely roughened to finish the top surfaces of the concrete bases. In the three-dimensional modeling via the ABAQUS solver, the Cohesive Zone Model (CZM) is used to simulate the interface shear failure. It is observed that the interface shear strength increases with the applied normal stress. The transversely roughened surface achieves the highest interface shear strength compared with those finished with the indented and smooth approaches. The smooth and indented surfaces are controlled by the adhesive failure mode while the transversely roughened surface is dominated by the cohesive failure mode. Also, it is observed that the CZM approach can accurately model the interface shear failure with 3–29% differences between the modeled and the experimental test findings.